Lesional mesial temporal lobe epilepsy and limited resections: prognostic factors and outcome. Issue 11 (15th October 2004) - Clusmann, H; Kral, T; Fackeldey, E; Blümcke, I; Helmstaedter, C; von Oertzen, J; Urbach, H; Schramm, J
Abstract : Objectives: To evaluate the influence of clinical, investigational, surgical, and histopathological factors on postoperative seizure relief in patients with mesial temporal lobe epilepsy (MTLE) due to lesions other than ammonshornsclerosis (AHS). Methods: Of 738 patients operated for TLE, 78 patients underwent limited resections for lesional MTLE (1990–2000). Seventy four patients with a follow up of more than one year were included. The preoperative clinical, neuropsychological, electroencephalogram, and neuroimaging characteristics were prospectively collected in a database. The histopathological material was re-examined. Results: The mean follow up was 49 months. Fifty eight patients were classified as seizure free (78.4% Class I), and six as almost seizure free (8.1% Class II), grouped together as satisfactory seizure control (64 patients, 86.5%). Five patients (6.8%) were categorised in Classes III and IV, respectively. These were grouped as unsatisfactory seizure control (10 patients, 13.5%). Surgical procedures were: 32 amygdalohippocampectomies (AH), 17 partial anterior AH, 15 AH plus polar resection, seven AH plus basal resection, and three AH plus extended temporal lesionectomy. There was no mortality and 2.7% mild permanent morbidity. Seizure relief did neither differ significantly with these approaches, nor with different classes of pathological findings (43 developmental tumours, 12 glial tumours, 10 dysplasias, and nine others). Even operation of dysplasias resulted in 80% satisfactory seizure control. Seizure onset during childhood proved to be a negative predictor for seizure relief (p = 0.020). MRI revealed 73 suspected lesions (98.6%), one dysembryoplastic neuroepithelial tumour was missed, in four cases no structural abnormalities could be confirmed with histopathological exam. Additionally, multifactorial regression revealed the factors "seizure onset after 10 years of age", "presence of complex partial seizures", "absence of a neurological deficit", and a "correlating neuropsychological deficit" as predictive for satisfactory seizure control. Conclusions: "Preoperative tailoring" resulting in limit resections has proven to be safe and to provide a very good chance for satisfactory seizure relief in patients with lesional MTLE.